Peanut Variety Performance in Florida 2002-2005 - Barry L. Tillman; Daniel W. Gorbet; H. C. Wood; Mark W. Gomillion; J. McKinney (EDIS)
Variety choice is a critical management decision for peanut production. There are several good peanut varieties to choose from today. This document is SS-AGR-13, one of a series of the Agronomy Department, UF/IFAS Extension. Originally published as Marianna NFREC Research Report 06-1. Publication date January 2006.